1997
DOI: 10.1346/ccmn.1997.0450406
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure Refinement and Mössbauer Spectroscopy of an Ordered, Triclinic Clinochlore

Abstract: Abstract_---The crystal structure of a natural, ordered llb-4 triclinic clinochlore has been refined in space group C1 from 4282 unique X-ray intensity measurements of which 3833 are greater than 3 times the statistical counting error (3~). Unit cell parameters are a = 5.3262(6) ,~; b = 9.226(1) A; c = 14.334(3) ,~; c~ = 90.56(2)~ [~ = 97.47(2)~ and ~/ = 89.979(9) ~ which represents the greatest deviation from monoclinic symmetry yet recorded for a triclinic chlorite. The final weighted R is 0.059 for reflecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 24 publications
3
28
0
Order By: Relevance
“…A representative sample of M26 glaucophanite (1 cm 3) was powdered with an agate mortar and a powder diffraction pattern was collected using Cu Kc~ radiation, from 5 ° to 70 °, in steps of 0.01 ° and 3 seconds per step. A quantitative phase analysis using the Rietveld method was performed using a richterite (Hawtorn et al 1997) and a clinochlore (Smyth et al 1981) as starting structural models. The atomic fractions were deduced from chemical analysis.…”
Section: Mineral Chemistry and Quantitative Diffraction Analysesmentioning
confidence: 99%
“…A representative sample of M26 glaucophanite (1 cm 3) was powdered with an agate mortar and a powder diffraction pattern was collected using Cu Kc~ radiation, from 5 ° to 70 °, in steps of 0.01 ° and 3 seconds per step. A quantitative phase analysis using the Rietveld method was performed using a richterite (Hawtorn et al 1997) and a clinochlore (Smyth et al 1981) as starting structural models. The atomic fractions were deduced from chemical analysis.…”
Section: Mineral Chemistry and Quantitative Diffraction Analysesmentioning
confidence: 99%
“…Interlayer bonding involves only hydrogen bonds; onethird of the atoms in chlorite are involved in hydrogen bonding, and it is this major structural feature that is the subject of the present study. The long-and short-range cation-ordering behavior of chlorites is now well understood from recent X-ray and spectroscopic studies (e.g., Rule and Bailey 1987;Welch et al 1995;Smyth et al 1997), which have shown that [6] Al is at M4 and [6] Mg is ordered at M3 (M3:M4 = 2:1). In end-member clinochlore, M1 and M2 sites of the 2:1 layer are filled by [6] Mg. A 29 Si MAS NMR study of synthetic monoclinic (C2/m) end-member clinochlore by Welch et al (1995) showed that there is a high degree of Al-Si short-range order within the tetrahedral sheet, as is also found in phlogopite and related micas (Herrero et al 1987;Circone et al 1991).…”
Section: Chlorite Structurementioning
confidence: 99%
“…in both studied crystals occurs in tetrahedral sites, but in purple chlorite it is also present in the octahedral sheet. Doublet D4 has IS and QS parameters that are characteristic of the M4 site (Smyth et al 1997 ) a lower quadropole splitting means more distortion around a site, the measured doublets D1 were ascribed as originating from the M1 site. However, the majority of ferrous ions occupy M2 sites in purple and green Cr-clinochlore.…”
Section: Resultsmentioning
confidence: 95%
“…ions are present in M1 and M2 crystal sites, and Fe 3? ions are present in M3 and M4 crystal sites, as well as in a tetrahedral coordination (Goodman and Bain 1979, Blaauw et al 1980, Dyar 1987, deGrave et al 1987, Gregori and Mercader 1994, Smyth et al 1997. The influence of Al 3?…”
Section: Introductionmentioning
confidence: 99%